Handlungskompetenzen des Religionslehrers und Katecheten ... , eine an der Vermittlung pädagogischer und katechetischer Fähigkeiten orientierte Ausbildung - Józef Stala (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
RE teachers are required to demonstrate the professional, theological, psychological and pedagogical knowledge and skills delineated in professional and institutional standards to facilitate the process of learning and upbringing. True respect for the pupils does not only call RE teacher for the adaptation of the teaching method, but also demands to develop many skills and undertake the emotional, intellectual, personal and religious formation. Handlungskompetenzen (the action- related competencies) seems to be very important for every teacher, but especially for RE teacher and catechist, because they are influenced by teacher’s beliefs and values. These competencies are the complex abilities needed to enact spontaneously specific knowledge in learning situation. This paper highlights the importance of the teachers’ actions or reactions in critical and/or challenging teaching/learning situations and ability to explain a topic in the response to pupils’ difficulty and questions. Equipping RE teachers and catechists to meet the needs of diverse pupils means also to help them in planning the educational actions and critical evaluation of didactical processes. Consequently, RE teacher or catechist needs to be not only a teacher, but also pedagogue and faith witness. Therefore, he/she should be characterized by a willingness to lifelong learning, enthusiasm for self-study and broad mindedness.